2014
DOI: 10.1001/jama.2014.9087
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Providing Conditional Economic Compensation on Uptake of Voluntary Medical Male Circumcision in Kenya

Abstract: IMPORTANCE Novel strategies are needed to increase the uptake of voluntary medical male circumcision (VMMC) in sub-Saharan Africa and enhance the effectiveness of male circumcision as an HIV prevention strategy. OBJECTIVE To determine whether small economic incentives could increase circumcision prevalence by addressing reported economic barriers to VMMC and behavioral factors such as present-biased decision making. DESIGN, SETTING, AND PARTICIPANTS Randomized clinical trial conducted between June 22, 2013… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
134
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(139 citation statements)
references
References 31 publications
5
134
0
Order By: Relevance
“…Although one should treat sensitive self-reported data from adolescents with caution (Plummer, Ross & Wight 2004), it was encouraging that strong evidence of an effect was also observed when assessing self-reported VMMC uptake at follow-up. The absolute and relative effects observed were similar to those observed for the middle-tier intervention group (US$8.75) in a 2013 trial assessing the effect of conditional economic compensation for VMMC uptake in Kenya (Thirumurthy, Masters & Rao 2014).…”
Section: Discussion and Actionable Findings For Policy Implementatiosupporting
confidence: 65%
See 1 more Smart Citation
“…Although one should treat sensitive self-reported data from adolescents with caution (Plummer, Ross & Wight 2004), it was encouraging that strong evidence of an effect was also observed when assessing self-reported VMMC uptake at follow-up. The absolute and relative effects observed were similar to those observed for the middle-tier intervention group (US$8.75) in a 2013 trial assessing the effect of conditional economic compensation for VMMC uptake in Kenya (Thirumurthy, Masters & Rao 2014).…”
Section: Discussion and Actionable Findings For Policy Implementatiosupporting
confidence: 65%
“…Existing evidence has shown that demand creation interventions are urgently needed (Wouabe 2013;) and can effectively increase VMMC uptake (Thirumurthy, Masters & Rao 2014;Mahler et al 2011;DeCelles & Ndlovu 2013). This study contributes to literature on the effectiveness of sport-based HIV prevention at schools as a scalable, innovative approach for VMMC demand creation in Zimbabwe.…”
Section: Sport For Developmentmentioning
confidence: 99%
“…For example, incentivizing people to come to testing events may have the potential to increase turnout, based on research that small monetary incentives can increase rates of voluntary medical male circumcision and returning for HIV test results. 59,60 …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, once the incentives were removed, engagement in care fell dramatically at the 18-month visit, suggesting that basic support would be needed to maintain clinical care continuity. High attrition may not be an issue with interventions that occur at a single visit (e.g., male circumcision) [40]; yet among sex workers it is imperative to link them to regular care and treatment for STI/HIV, requiring continual follow-up, which may not be easily attained without material motivators. At the same time, new research questions emerge: Are other combinations of incentives and conditionalities more effective?…”
Section: Discussionmentioning
confidence: 99%